Liquidity Ratio, Profitability, And Solvency On Stock Returns With Capital Structure As An Intervening Variable (Study On Food And Beverage Sub Sector Listed In Indonesia Stock Exchange (Idx) Period 2013-2017) - Chasanah, Nailul; Sucipto, Agus (Universitas Dr. Soetomo, 2019)
The stock market is a business field of securities trading one of them stock. For prospective investors, investment decisions in stock must be preceded by a process of analysis of variables which can influence the price of a stock. Investors need to have benchmarks in order to know whether if he invested in a company he would benefit if the shares are sold. Salaah one factor to be a benchmark investor is knowing the financial condition of the company where it can be seen with the financial ratio analysis and management of an optimal capital structure. This study aims to determine the effect of the ratio of liquidity, profitability, and solvency to return stock with a capital structure as an intervening variable.This study uses a quantitative approach. The research method using the method of documentation. Samples were company food and beverage sub-sectors listed in Indonesia Stock Exchange 2013-2017 period. The sampling technique used purposive sampling method with predetermined criteria obtained 11 samples of the company. This study uses data analysis Partial Least Square (PLS).These results indicate that liquidity ratios have a negative impact on stock returns, while the profitability and solvency ratios have no effect on stock returns. The results also show the liquidity ratio and solvency ratio has a negative effect on the capital structure, profitability ratios while not having capital structure. And capital structure has a negative impact on stock returns. The results also show the ratio of liquidity, profitability, and solvency partially no effect on stock returns with the capital structure as an intervening variable.